Impact of Variation in Estimated Quantity Clauses on Allocating Financial Risks in Measurement Contracts - Alhyari, Omar (2021)
Unit price contracts are awarded to contractors based on estimated quantities of work, while payments to contractors are based on the actual quantities performed. Deviations between such estimated and actual quantities expose contractors and owners to various amounts of financial risks. In order to reduce those risks, variation in estimated quantity (VEQ) clauses are usually found in construction contracts. There is a need to support contractors in analyzing and quantifying the financial risks associated with the terms of the applicable changed quantity clauses. This paper presents a review of the terms of VEQ clauses included in public construction contracts. Then the paper examines the impact of VEQ clauses on the distribution of financial risks associated with changes in quantities between the owner and the contractor. The paper shows significant inconsistencies between the terms and stipulations of variation in estimated quantity clauses adopted by different US public construction authorities and international construction contract forms. An illustrative example is provided to highlight and quantify the varying amounts of risks incurred by contractors, depending on the terms and conditions of the variation in estimated quantity clause imposed by the contracting public authority in the construction contract. Contractors should be able to identify and quan tify these risks before submitting their bid offers. The performed analysis should prove to be useful to the contracting parties and can reduce the potential for disputes related to changes in quantities of work.